Late Roman C wares discovered at Histria in the Acropolis Centre-South sector (2013 and 2014) - Iliescu, I.; Bottez, V.; Țârlea, A.; Lițu, A.; Bivolaru, A. (Materiale și Cercetări Arheologice)
132 pottery fragments, discovered in the first two years of archaeological research in the Acropolis Centre-South Sector (excavation coordinated by a team from the University of Bucharest), at Histria are published in this paper. This pottery lot contains ten forms with 18 types of kitchen ware. This category of artefacts offers important information concerning the ACS Sector’s chronology and the economic relations of Histria (and of Scythia Minor) during the Late Roman period.